The Future of Ruins: Remains, Industrial Suburbs and Temporary Uncertainties in Sergio Chejfec's Boca de lobo - Guerra, Juan José (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Analyzing the “geographical anatomy of industrial urbanism” (Soja) in Boca de lobo, by Sergio Chejfec, is carried out on this paper to understand this novel. In this piece is performed a suburb as an organized place close to the factory. It is proposed that the alignment of the industrial landscape in this work depends on an imaginary of the ruins. Likewise, the multiplication of ostensible signs of deterioration is combined, particularly, with a dialogue with strong discursive traditions, mainly Marxism and social realism. It is maintained that dealing with the ruins in Boca de lobo tends to articulate material vestiges with textual fragments, and in this sense the construction of urban space is carried out both in relation to what is seen (material ruins) and what is read (textual quotes). In short, the novel builds an urban space whose referential indices refer to different historical times and textual traditions through a montage of heterochronic temporalities.